Public Financing of Business Innovation in Boyacá Colombia: A Case Study - Díaz-Goyeneche, Sandra Lorena; Cruz-Vásquez, José Luis; Becerra Gualdron, Claudia Jessenia (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Boyacá state currently presents low levels of innovation affecting directly on its economic growth and sustainability of its companies. This article studies the case of two companies that had direct access to public resources for the promotion of innovation, with the aim of analyzing the influence of said investment on the general and innovative performance of the company and its contribution to the economic growth of the state. Through the case study methodology, three stages were proposed, firstly, an analysis model was built that allowed the construction of quantitative and qualitative indicators; secondly, this model was applied in two companies that had access to resources through public calls for the execution of innovation projects. Third and last, some recommendations were presented to the stakeholders to increase the efficiency of the investment of these resources.